Development and application of the discrete model of multi-layered textile materials - Shchutska, Ganna (Eastern-European Journal of Enterprise Technologies, 2016)
The discrete method of modeling the fluid passage through the textile material was developed, which makes it possible to define the boundary of the wetted section of material both at the surface and in the depth for materials with an arbitrary number of layers. The essence of the proposed method lies in modeling the material with a system of cells and passages for spreading the fluid with the assigned characteristics. Preliminary studies substantiated the relevance of this method, which was applied for studying a specific material. Such studies are necessary for the correct prediction of the processes that occur in therapeutic textile materials. They also create prerequisites for designing materials with the required properties. We revealed the effect of additional concentrations inside the material, the consideration of which makes it possible to correctly predict the dynamics of fluid passage through textile material. An analysis of functional dependences of the boundary of the wetted zone for two–layered fabrics, which are used for therapeutic purposes, allowed us to recommend it in the form of the sum of exponential function and exponential function with the maximum. Each two-layered material in this case is characterized by four constants in the course of the fluid passage. The actual characteristics of two-layer textile material were defined. They are used for determining the fluid concentration in the lower layer of material. This makes it possible to predict the period of using material as a therapeutic textile system. The use of the proposed method for multi–layer materials makes it possible to select the most rational characteristics of separate components for a specific case